Exploring the Relevance of Teacher Education at Tribhuvan University - Panthee, Shree Krishna; Khanal, Sanjib Raj; Adhikari, Keshab Sharma (Journal of TESON, 2026)
This study aims to examine the relevance of teacher education (TE) programs conducted by Tribhuvan University (TU), Nepal, using a methodological approach that combines phenomenology and empirical inquiry. It delves into the discrepancies between the TE syllabuses and participants' actual experiences through a series of qualitative methods, including interviews, content analysis, and focus group discussions (FGDs), while maintaining the study's credibility, reliability, and ethical standards. The study reveals that the TES programs at TU are quite far from the requirements for the Teachers Service Commission (TSC) Licensure Exams, which demand candidates to study independently other areas such as general knowledge and legal aspects that go beyond the EO curriculum. Recent policy changes have allowed graduates from any discipline to get a teaching license, thus solving the issue of teacher shortage, but at the same time reducing the quality. The issues of teacher hiring and appraisal that lacked equity also made the situation worse. Theoretical aspects are still more emphasized in teacher education programs offered by universities. However, there has been a lack of sufficient training and experience along with such theoretical matters, and unorganized coordination among stakeholders has further worsened this situation. Along with these, B. Ed courses are also lacking. The curriculum does not offer rigorous practical pedagogy and technology integration. The article explains how the gap between theory and practice can be closed if the duration of the internship is increased, course harmony improved, hands-on teaching methodologies introduced, and professionals allowed to continue their training. This paper also calls for enhanced incentives and curriculum reforms that integrate the latest in technology and innovations. For the proposed measures to take place, the paper highlights the need for a string of reforms and institutional collaboration between TU and the TSC.